The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1001/archderm.138.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Urticaria Pigmentosa in Adult Patients With Systemic Mastocytosis

Abstract: To determine clinical correlates of urticaria pigmentosa (UP) regression in adult patients with systemic mastocytosis (SM).Design: Cohort study of the natural history of mastocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…6,10,21,22 Mean tryptase levels have been discussed in prior studies to vary between 1 to 15 g/L in healthy control subjects, which reflect very well the results of our control group with an average tryptase level of 5.70 g/L. 21 A level greater than 20 g/L is strongly suggestive of a systemic mast cell disease, and has been included as minor criterion in the diagnosis of systemic mastocytosis (Table II).…”
Section: Discussionsupporting
confidence: 82%
“…6,10,21,22 Mean tryptase levels have been discussed in prior studies to vary between 1 to 15 g/L in healthy control subjects, which reflect very well the results of our control group with an average tryptase level of 5.70 g/L. 21 A level greater than 20 g/L is strongly suggestive of a systemic mast cell disease, and has been included as minor criterion in the diagnosis of systemic mastocytosis (Table II).…”
Section: Discussionsupporting
confidence: 82%
“…In adults, the prognosis of indolent systemic mastocytosis is generally good, and in approximately 10% of the patients who have systemic mastocytosis for more than 10 years, urticaria pigmentosa may even regress [20]. In a study of 145 consecutive adult patients observed for a median of 147 months (range, 61-329 months), only 5 (3%) showed progression to a more aggressive form of the disease (aggressive systemic mastocytosis; systemic mastocytosis with an associated hematologic, non-mast cell lineage disease; or mast cell leukemia) [21••].…”
Section: Prognosismentioning
confidence: 99%
“…Persistent CM of childhood and adulthood can lead to SM [22]. However, regression of UP in adult patients with ISM may or may not be accompanied by systemic disease improvement [23].…”
Section: Cutaneous Signs and Symptomsmentioning
confidence: 99%